EMANCIPATION OF PROFESSIONAL ACTIVITIES OF A TEACHER ASSISTANT IN THE PROCESS OF MENTORING AT PRE-SCHOOL INSTITUTION - Ciuciulkiene, Nijole; Tandzegolskienė - Bielaglovė, Ilona; Anglickienė, Ruta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
When discussing the assistant's emancipated participation in the educational process, it is important not to forget the pre-school teacher who often becomes a formal or informal mentor to the teaching assistant. It is the role of the mentor, his/her influence, that is one of the most important factors in the process of emancipation of the teaching assistant. Interrelationships based on support, respect, tolerance, sharing of experience and responsibility, constant help to each other, and support turn mentoring into a high-quality process that ensures emancipation. It is important that the mentor clearly defines what he/she expects from the assistant and is willing to help him/her to develop. Otherwise, it will not make sense to talk about the emancipation of the teaching assistant's professional activity. Relying on the qualitative research findings it is possible to state that a teacher assistant is supposed to provide a qualified support to an educator and a pupil in ordinary and inlusive educational process. It requires from teacher assistant vide range of competences,enabling him/her to demonstrate rationality, clear value system, professionalism, i.e. to be an emancipated personality. The process of emancipation takes place when there is the harmony among the set of emancipatory legal, philosophical, social, and educational aspects and the personal reality perception, activity and will. In order to develop the emancipation of a teacher assistant's, the competence of the mentor plays the key role, especialy his/her abilities to encourege and empower the mentee‘s independent, still community - directed solutions. Thus, the reversity of the mentoring process comes to the focus of the attention. The proof of the teacher assistant's emancipation success is considered to be the process of reverse mentoring. The qualitative content analysis of the interviews of the teaching assistants working in pre-school education institutions revealed that the emancipation of teaching assistants is observed in the answers of all informants, but the emancipation of their activities in the mentoring process is only partially ensured.